2021
DOI: 10.1002/ctm2.449
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits lipid accumulation to repress prostate cancer progression by mediating the epigenetic modification of CES1

Abstract: Background Androgen deprivation therapy (ADT) is the main clinical treatment for patients with advanced prostate cancer (PCa). However, PCa eventually progresses to castration‐resistant prostate cancer (CRPC), largely because of androgen receptor variation and increased intratumoral androgen synthesis. Several studies have reported that one abnormal lipid accumulation is significantly related to the development of PCa. Melatonin (MLT) is a functionally pleiotropic indoleamine molecule and a key re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 83 publications
0
29
0
1
Order By: Relevance
“…Therefore, it seems possible that every cell harbors MT1 and/or MT2 receptors. Many of the functions of melatonin in modulating oncogenic transformation are mediated by signaling events that follow the binding of melatonin to its membrane receptors [2,7,130,131].…”
Section: Melatonin Signaling Via the Cellular Membrane Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems possible that every cell harbors MT1 and/or MT2 receptors. Many of the functions of melatonin in modulating oncogenic transformation are mediated by signaling events that follow the binding of melatonin to its membrane receptors [2,7,130,131].…”
Section: Melatonin Signaling Via the Cellular Membrane Receptorsmentioning
confidence: 99%
“…Melatonin has long been known to be an endogenously produced anti-cancer agent [1][2][3][4][5][6][7][8]. This action has been confirmed for multiple tumor types [9][10][11][12][13][14] and in both in vitro [15][16][17][18] and in vivo [19][20][21][22][23][24][25][26] studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is urgent to find new cost-effective therapeutic alternatives with fewer side effects. A mechanistic study revealed that melatonin reduces PC progression to CRPC by decreasing lipid accumulation and activity in PC cells via upregulating the lipid metabolism-related gene carboxylesterase (CES) 1 in PC cells [27].…”
Section: Review Melatonin's Oncostatic Effect On Prostate Cancermentioning
confidence: 99%
“…Excessive lipids are then usually stored in lipid droplets (LDs) as neutral lipids (mainly triglycerides (TGs) and cholesterol esters (CEs)). Indeed, LD accumulation is widely observed in many human malignancies such as prostate cancer ( 43 ), glioblastoma ( 44 ) and ovarian cancer ( 45 ). It’s increasingly considered as an emerging hallmark of cancer aggressiveness, especially in tumor cells exposed to nutrient deprivation and hypoxia ( 46 , 47 ).…”
Section: Alterations Of Lipid Metabolism In Tumor Cellsmentioning
confidence: 99%